TRIBUTES TO JEAN BARMAN, MENTOR AND SCHOLAR EXTRAORDINAIRE. (BC Studies)
The article offers information on the tributes paid to scholar and mentor Jean Barman, emphasizing her profound influence on generations of students, colleagues, and Indigenous communities. Topics discussed include her groundbreaking contributions to Indigenous education and history, her mentorship that empowered Indigenous scholars—especially women—and her lasting legacy in advancing decolonizing approaches within academic and community spaces.